Analisis Kesehatan Keuangan BUMN Untuk Melihat Keberlanjutan Perusahaan Di Masa Datang Pada PT. Garuda Indonesia (Persero) Tbk. - Maretta A’yun Masitoh; Iwan Setya Putra (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2020)
The research objective is to analyze the financial performance of PT. Garuda Indonesia (Persero) Tbk is based on financial statements for the period 2014-2018. Using a quantitative method approach by calculating the ratio in the company. The results of the current ratio research decreased in 2017 and 2018, the Solvency Ratio reached the position of extreme leverage in 2018, the activity ratio analysis showed that the financial position of PT Garuda Indonesia (Persero) Tbk in 2014-2015 the average age of its receivables increased, the analysis of profitability ratios and the value of profit margins counted very small because the expenditure is quite large and results in a healthy condition, the average analysis of the Z score from 2014 - 2018 is 1.6, the figure can be categorized in areas prone to bankrupt or gray areas. It is expected that PT. Garuda Indonesia (Persero) Tbk can pay attention and analyze financial ratios that are generated based on periodic financial statements, so that PT. Garuda Indonesia can increase finance significantly